Predicting sudden cardiac death using common genetic risk variants for coronary artery disease - Hernesniemi, Jussi A.; Kleber, Marcus E.; März, Winfried (European heart journal, 2015)
Aims: Genome-wide association studies (GWAS) have identified many variants associating with an increased risk of coronary artery disease (CAD). We studied the possible association between these variants and the risk of sudden cardiac death (SCD).Methods and results: A weighted genetic risk score (GRSCAD) was formed from variants most strongly associating with CAD identified by the CARDIoGRAMplusC4D Consortium explaining 10.6% of the heritability of CAD [153 single-nucleotide polymorphisms with r2 < 0.2]. The association between GRSCAD and the occurrence of SCD was studied in three independent autopsy series of consecutive cases combining altogether 1035 autopsies with 306 SCDs due to CAD (SCDCAD). The results were replicated in a prospective follow-up study of 2321 patients (mean follow-up time of 6.2 years with 48 incident SCDs of which 39 due to CAD) undergoing clinical exercise test at baseline. In a meta-analysis of the autopsy series, GRSCAD associated significantly with the risk of SCDCAD with age, body mass index, and sex adjusted odds ratio (OR) of 1.042 (1.023-1.061, P = 9.1 × 10−6) for one allele increase in GRSCAD. The same association was seen in both sexes. GRSCAD predicted significantly the risk of SCDCAD also in a prospective study setting (Cox regression analysis adjusted with all relevant clinical data): hazard ratio 1.049 (1.010-1.090, P = 0.014). In meta-analysis of all cohorts (adjusting further for other genetic markers related to traditional risk factors and QT-interval), the association was highly significant [OR 1.045 (1.028-1.063), P = 1.7 × 10−7]. Conclusion: Genetic risk estimate for CAD may also be used to predict SCD.
Gesehen am 22.01.2018